Associations between cuprotosis‐related genes and the spectrum of metabolic dysfunction‐associated fatty liver disease: An exploratory study - Yuan, Hai‐Yang; Liu, Wen‐Yue; Feng, Gong; Chen, Sui‐Dan; Jin, Xin‐Zhe; Chen, Li‐Li; Song, Zi‐Jun; Li, Ke; Byrne, Christopher D.; Targher, Giovanni; Tian, Na; Li, Gang; et al. (Diabetes, obesity & metabolism, 2024)
Aims To explore the associations between cuprotosis‐related genes (CRGs) across different stages of liver disease in metabolic dysfunction‐associated fatty liver disease (MAFLD), including hepatocellular carcinoma (HCC). Materials and Methods We analysed several bulk RNA sequencing datasets from patients with MAFLD (n = 331) and MAFLD‐related HCC (n = 271) and two MAFLD single‐cell RNA sequencing datasets. To investigate the associations between CRGs and MAFLD, we performed differential correlation, logistic regression and functional enrichment analyses. We also validated the findings in an independent Wenzhou PERSONS cohort of MAFLD patients (n = 656) used for a genome‐wide association study (GWAS). Results GLS, GCSH and ATP7B genes showed significant differences across the MAFLD spectrum and were significantly associated with liver fibrosis stages. GLS was closely associated with fibrosis stages in patients with MAFLD and those with MAFLD‐related HCC. GLS is predominantly expressed in monocytes and T cells in MAFLD. During the progression of metabolic dysfunction‐associated fatty liver to metabolic‐associated steatohepatitis, GLS expression in T cells decreased. GWAS revealed that multiple single nucleotide polymorphisms in GLS were associated with clinical indicators of MAFLD. Conclusions GLS may contribute to liver inflammation and fibrosis in MAFLD mainly through cuprotosis and T‐cell activation, promoting the progression of MAFLD to HCC. These findings suggest that cuprotosis may play a role in MAFLD progression, potentially providing new insights into MAFLD pathogenesis.